Công thức biến đổi tổng thành tích

Hướng dẫn giải

\(cosx + cosy = 2cos\dfrac{x + y}{2} cos\dfrac{x - y}{2}\)

\(cosx - cosy = -2sin\dfrac{x + y}{2}sin\dfrac{x - y}{2}\)

\(sinx + siny = 2sin\dfrac{x + y}{2} cos\dfrac{x - y}{2}\)

\(sinx - siny = 2cos\dfrac{x + y}{2} sin\dfrac{x - y}{2}\)

\(tanx + tany = \dfrac{sin (x + y) }{cosx.cosy}\)

\(tanx - tany = \dfrac{sin (x - y) }{cosx.cosy}\)

\(cotx + coty = \dfrac{sin (x + y) }{sinx.siny}\)

\(cotx - coty = \dfrac{sin (y - x) }{sinx.siny}\)

  Đặc biệt:  

  • \(sinx + cosx = \sqrt{2} sin(x + \dfrac{x} {4}) = \sqrt{2} cos(x - \dfrac{x} {4})\)
  • \(sinx - cosx = \sqrt{2} sin(x - \dfrac{x} {4}) = -\sqrt{2} cos(x +\dfrac{x} {4})\)
  • \(1 \pm sin2x = (sinx \pm cosx)^2\)
Tags công thức biến đổi tổng thành tích biến đổi tổng thành tích công thức biến đổi

Có thể bạn quan tâm